Making a Difference Strategies for Scaling Social Innovation for Greater Impact - FRANCES WESTLEY (2010)
This article explores the strategies and dynamics of scaling up social innovations. Social innovation is a complex process that profoundly changes the basic routines, resource and authority flows, or beliefs of the social system in which it occurs. Various applications of marketing and diffusion theory are helpful to some extent in understanding the trajectories or successful strategies associated with social innovation. It seems unwise, however, to rely solely on a market model to understand the dynamics of scaling social innovation, in view of the complex nature of the supply-demand relation with respect to the social innovation market. Instead, the authors propose a distinctive model of system transformation associated with a small but important group of social innovations and dependent on discontinuous and cross-scale change. This paper focuses on the challenge of scaling up social innovations in general and in particular the dynamics of going to scale